2018
DOI: 10.1101/325316
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Messenger RNAs transcribed from yeast linear cytoplasmic plasmids possess unconventional 5’ and 3’ UTRs and suggest a novel mechanism of translation

Abstract: Linear plasmids with almost identical compact genetic organization have been found in the cytoplasm of yeast species from nine genera. We employed pGKL1,2 plasmids from Kluyveromyces lactis as a model to investigate the previously unstudied transcriptome of yeast cytoplasmic linear plasmids. We performed 5' and 3' RACE analysis of all the pGKL1,2 mRNAs and found them not 3' polyadenylated and containing mostly uncapped 5' poly(A) leaders that are not complementary to the plasmid DNA. The degree of 5' capping a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 130 publications
(156 reference statements)
0
7
0
Order By: Relevance
“…Next, we wished to characterize transcription initiation of the VLE genes. Our previous 5′ RACE-PCR experiments had revealed 5′ cap structures on the VLE-specific mRNAs, likely synthetized by VLE-encoded K2ORF3p mRNA capping enzyme, and also the presence of non-templated 5′ poly(A) leaders of heterogeneous lengths in mRNAs of 12 pGKL genes except for K2ORF2 , K2ORF3 and K2ORF8 [ 36 ]. Interestingly, heterogeneous 5′ poly(A) leaders are a known feature of poxviral intermediate and late transcripts [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Next, we wished to characterize transcription initiation of the VLE genes. Our previous 5′ RACE-PCR experiments had revealed 5′ cap structures on the VLE-specific mRNAs, likely synthetized by VLE-encoded K2ORF3p mRNA capping enzyme, and also the presence of non-templated 5′ poly(A) leaders of heterogeneous lengths in mRNAs of 12 pGKL genes except for K2ORF2 , K2ORF3 and K2ORF8 [ 36 ]. Interestingly, heterogeneous 5′ poly(A) leaders are a known feature of poxviral intermediate and late transcripts [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we concluded that slippage of VLE RNAP at the initiation site was the mechanism responsible for 5′ polyadenylation of the transcripts. Moreover, the identified INR sequence constituted an independent DNA element, not influenced by the sequence of the gene because the pattern of the sequenced 5′ RACE-PCR clones for K1ORF2 transcripts was the same as for G418 R transcripts produced from the K1UCR2 with the wt INR [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cytosolic presence and activity of RNA polymerase III for transcription of exogenous DNA has been detected (20, 21). Also, it has been recently evidenced that mRNAs can be transcribed from plasmids in yeast cytoplasm (22). Although cytosolic expression of mRNA from exogenous DNA has not been explored, the current study provided evidences which indicate cytosolic presence of the transgene may be enough for the transgene expression.…”
Section: Discussionmentioning
confidence: 99%